The role of estrogen in cardiac transplantation: mechanistic insights and effects on clinical outcomes - Wolff von Gudenberg, Rosalie; Kupsch, Constantin; Gilles, Linda; Xiao, Yao; Ortiz-Koh, Catalina; Ruhparwar, Arjang; Zhou, Hao; Tullius, Stefan G. (Frontiers in Transplantation, 2026)
Sex hormones profoundly shape immune responses and influence outcomes after heart transplantation. Estrogen enhances allosensitization and is associated with a higher incidence of acute rejection in female recipients. Beyond its immunological effects, estrogen also modulates the pharmacokinetics and pharmacodynamics of calcineurin inhibitors—particularly cyclosporine A—thereby influencing immunosuppressive efficacy and early graft performance. Donor–recipient sex mismatch further modulates transplant outcomes. Female-to-male transplants in particular exhibit the poorest short- and long-term survival and show increased rates of primary graft failure and cardiac allograft vasculopathy. Mechanistic and experimental data provide a biological basis for these observations: estrogen protects the myocardium against ischemia–reperfusion injury and preserves vascular integrity through both nuclear estrogen receptors and GPER-mediated signaling. Abrupt withdrawal of this estrogen-mediated protection in male recipients of female donor hearts may therefore increase susceptibility to early graft dysfunction and chronic vasculopathy. Integrating sex and hormonal status into transplant medicine—through hormonal profiling, receptor-specific mechanistic studies, and sex-adapted immunosuppressive strategies—may pave the way toward more individualized and effective therapeutic approaches in heart transplantation.